2015
DOI: 10.1186/s12879-015-1050-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infection in critically ill patients with secondary and tertiary peritonitis: epidemiology, microbiology and influence in outcomes

Abstract: BackgroundSurgical site infection (SSI) remains a significant problem in the postoperative period that can negatively affect clinical outcomes. Microbiology findings are typically similar to other nosocomial infections, with differences dependent on microbiology selection due to antibiotic pressure or the resident flora. However, this is poorly understood in the critical care setting. We therefore aimed to assess the incidence, epidemiology and microbiology of SSI and its association with outcomes in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 23 publications
(49 reference statements)
9
23
0
2
Order By: Relevance
“…In our study, 2 nd group carbapenems showed the highest in vitro efficacy in both study groups, corresponding to data of other colleagues [29]. Other clinicians call to diminish/ignore the use of any generation cephalosporins due to serious drop of their efficacy with time and strong promotion of antibacterial resistance [26].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our study, 2 nd group carbapenems showed the highest in vitro efficacy in both study groups, corresponding to data of other colleagues [29]. Other clinicians call to diminish/ignore the use of any generation cephalosporins due to serious drop of their efficacy with time and strong promotion of antibacterial resistance [26].…”
Section: Discussionsupporting
confidence: 88%
“…Antibiotic resistance to >2 antibiotics Original Research Article: full paper (2017), «EUREKA: Health Sciences» Number 6 occurred in 64,9 % of cases of SP, presented mainly by extended spectrum b-lactamase-producing Enterobacteriaceae spp. and P. aeruginosa in 11,1 % and 11,9 % respectively [26]. In other works, fraction of nosocomial MDR reached 84,8 %, but just 14 % in case of TP [23].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…complications, however it was not common in other sepsis-related complications; *IQR not calculated because < 5 values in range; †Several patients developed more than one sepsis-related complication.who have undergone abdominal surgery 24. The majority of organisms involve hospital acquired ESKAPE pathogens namely…”
mentioning
confidence: 99%
“…Klebsiella pneumoniae was the most prevalent organism during phase I (34.7%) whereas, Acinetobacter baumannii was the commonest organism during phase II (38.5%). In a study published by Ballus et al in 2015 35 E. coli (20.4%) and Candida spp. (17.1%) were the most frequently isolated microorganisms from SSIs and were associated with a higher incidence of antibiotic resistance (64.9%) in ICU patients.…”
Section: Discussionmentioning
confidence: 92%